Peningkatan Kualitas Pelayanan Publik Melalui Efektivitas Penetapan Capaian Kerja Strategis Pada Dinas Perhubungan Kabupaten Wonogiri - Widyani Sekar Ramadhania; Anggit Dyah Kusumastuti (JURNAL EKONOMI BISNIS DAN KEWIRAUSAHAAN, 2023)
: Strategic planning as a guideline that becomes a benchmark in responding to all challenges and problems that arise while managing the organization, so that strategic planning is carried out which is intended to be long term planning to reach a better future. The Department of Transportation of the Wonogiri Regency in carrying out information fulfillment, carries out planning in improving the quality of services in the transportation sector. Determining the right strategy can deliver orgabizational success in achieving goals and having a competitive advantage. The Department of Transportation of the Wonogiri Regency’s strtategic plan for 2021-2026 stipulates as many as 3 (three) performance indocators thathave been implemented in 2022 per June or quarter II with details of overall target achievement of 97,42% (very good category). In term of improving service quality through the community satisfaction index it achieved a value of 97,91% (very good category) and increased transportation safety and security through the traffic safety index achieved a value of 97,42% (very good category).